Co3V2O8 Nanorods embedded on 3D holey carbon boxes as hybrid anode material for LIBs. (November 2022) - Song, Xixin; Lu, Qian; Zhang, Bo; Tian, Runsai; Zhang, Hongbin; Lei, Tianyu; Guo, Wenjuan; Feng, Jijun
Highlights: A novel Co3 V2 O8 @HCB hybrid anode material is designed and fabricated. ZIF-67 derived hollow carbon with hierarchical pores and holes. 1D Co3 V2 O8 nanorods embedded on 3D holey carbon boxes. The synergistic effects contribute to superior electrochemical performances. Abstract: A novel composite, consisting of bimetal oxide Co3 V2 O8 with high Li + accommodation capacity and metal-organic framework derived conductive carbon skeleton (Co3 V2 O8 @HCB), is designed and fabricated through a facile process. Co3 V2 O8 nanorods are implanted on 3D holey carbon boxes to suppress aggregation and volume expansion during cycling, as well as take advantage of the superior conductivity of carbon support. Pseudocapacitance behavior of the unique nano-architecture furtherly promotes the lithium storage capacity and rate capability. As hybrid anode material, the synergistic effects endow the Co3 V2 O8 @HCB with distinguished electrochemical performance, which delivers a reversible capacity of around 1000 mAh·g −1 after 500 cycles at 1 A·g −1, together with an excellent rate capability of 648 mAh·g −1 at 5 A·g −1 . Graphical abstract: Image, graphical abstract